Comportamento de duas variedades e três linhagens de soja, em diferentes níveis de adubação fosfatada, em solos sob vegetação de cerrado, de Ituiutaba, MG, e Goiânia, GO - Barbosa Rolim, Renato; Braga, José Mário; Silva Reis, Múcio; Vasconcelos Costa, Alberto; Sigueyuki Sediyama, Carlos (Revista Ceres, 2025)
The purpose of this study was to verify the performance of two soybean varieties, Glycine max (L.) Merrill cvs. IAC-2’ and ‘UFV-1’, and three strains — ‘IAC-73-4013’, ’Vx4-101-1’ and ‘VX10-47-5-3-3’ — under four different levels of phosphorus application in cerrado soils at Ituiutaba, Minas Gerais, and Goiania, Goias, Brazil. Agronomic traits evaluated were: grain yield, plant height and weight of 100 seeds.